From pre-DP, post-DP, SP4, and SP8 Thymocyte Cell Counts to a Dynamical Model of Cortical and Medullary Selection - Sawicka, Maria; Stritesky, Gretta; Reynolds, Joseph; Abourashchi, Niloufar; Lythe, Grant; Molina-Paris, Carmen; Hogquist, Kristin (Frontiers in Immunology, 2014)
Cells of the mature $αβ$~T~cell repertoire arise from the development in the thymus of bone marrow precursors (thymocytes). $αβ$~T~cell maturation is characterised by the expression of thousands of copies of identical $αβ$~T~cell receptors and the CD4 and/or CD8~co-receptors on the surface of thymocytes. The maturation stages of a thymocyte are: (1) double negative (DN) (TCR$^{-}$, CD4$^{-}$ and CD8$^{-}$), (2) double positive (DP) (TCR$^{+}$, CD4$^{+}$ and CD8$^{+}$), and (3) single positive (SP) (TCR$^{+}$, CD4$^{+}$ or CD8$^{+}$). Thymic antigen presenting cells provide the appropriate micro-architecture for the maturation of thymocytes, which ``sense'' the signalling environment via their randomly generated TCRs. Thymic development is characterised by (i) an extremely low success rate, and (ii) the selection of a functional and self-tolerant T~cell repertoire. In this paper, we combine recent experimental data and mathematical modelling to study the selection events that take place in the thymus after the DN stage. The stable steady state of the model for the pre-DP, post-DP and SP populations is identified with the experimentally measured cell counts from 5.5-17 week old mice. We make use of residence times in the cortex and medulla for the different populations, as well as recently reported asymmetric death rates for CD4 and CD8 SP thymocytes. We estimate that 65.8% of pre-DP thymocytes undergo death by neglect. In the post-DP compartment, 91.7% undergo death by negative selection, 4.7% become CD4 SP and 3.6% become CD8 SP. Death by negative selection in the medulla removes 8.6% of CD4 SP and 32.1% of CD8 SP thymocytes, respectively. Approximately 46.3% of CD4 SP and 27% of CD8 SP thymocytes divide before dying or exiting the thymus.